Electronic charting of transfusion medicine consults: implementation, challenges and opportunities. Issue 5 (20th March 2020) - Mohammad, Mohammad K.; Wooten, Melanie S.; Maier, Cheryl L.; Hill, Charles E.; Guarner, Jeannette; Roback, John D.; Winkler, Anne M.; Sullivan, Harold C.
Abstract : Background: The Joint Commission lists improving staff communication (handoffs) as part of several National Safety Goals. In this study, we developed an electronic web‐based charting system for clinical pathology handoffs, which primarily consist of transfusion medicine calls, and evaluated the advantages over a paper‐based handwritten call log. Materials and Methods: A secure online web browser application using Research Electronic Data Capture (REDCap) was designed to document on‐call pathology resident consults. A year after implementation, an online survey was administered to our pathology residents in order to evaluate and compare the usability of the electronic application (e‐consults) to the previous handwritten call log, which was a notebook where trainees hand wrote different components of the consult. Results: The REDCap web‐based application includes discrete fields for patients' information, requesting physician contact, type of consult, action items for follow‐up and faculty responses, as well as other information. These components have eventually progressed to be an online consult call catalog. With approximately 1079 consults per year, transfusion medicine‐related calls account for ~90% of the encounters, while clinical chemistry, microbiology and immunology calls constitute the remainder. The overall response rate of the survey was 96% (29 of 30 participants). Of the 16 respondents who experienced both call log systems, 100% responded that REDCap was an improvement over the handwritten call log ( P  < 0·0001). Conclusion: E‐consult documentation entered into a web‐based application was a user‐friendly, secure clinical information access and effective handoff system as compared to a paper‐based handwritten call log.